New model phthalonitrile resin system based on self‐promoted curing reaction for exploring the mechanism of radical promoted‐polymerization effect. Issue 42 (19th June 2019) - Liu, Zhengzhou; Liu, Yang; Peng, Weifeng; Lu, Zheng; Liang, Bo; Liu, Yao; Li, Chengfeng; Hu, Jianghuai; Zeng, Ke; Yang, Gang
ABSTRACT: The reaction mechanism and product properties of radical promoted‐polymerization effect of phthalonitrile (PN) were further studied in this article. Different from the previous blending model system, this work provided a structurally symmetrical self‐promoted PN model compound [di‐imide PN model monomer (DAIM‐PN)], which was more conductive to study the polymerization mechanism. Combination of " in situ " infrared, proton nuclear magnetic resonance, and matrix‐assisted laser desorption/ionization time of flight mass spectrometry offered a clearer picture of polymerization mechanism. The results indicated that DAIM‐PN formed isoindoline and its cyclized tetramer of phthalocyanine selectively during the curing process. This work also demonstrated that the aliphatic chain participated in the reaction of nitrile group and provided more evidence for the reaction site (secondary carbon). Besides, high performance polymers with good processing properties, excellent thermal stability (overall char yield >74% at 800 °C, N2 ), and heat resistance ( T g > 470 °C) were obtained by blending and copolymerizing DAIM‐PN with 1, 3‐bis(3, 4‐dicyanophenoxy)benzene. The effectiveness and application potential of the reaction mechanism were confirmed. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48134. Abstract :